(untitled) (Journal of Parents and Teachers, 2014)
Fear, when it is a feeling referred to survival, is good, but when we lose control over fear, it is dangerous and may become a disease. Reaching security levels that our society has is the goal of the majority, but there are people who feel scared because they cannot reach those security levels. This article classifies fears in specific phobias, social phobias, posttraumatic stress, anxiety and anguish.